Sustainable Open Innovation between Large Companies and Startups - Cagnoli, Davide (My University, 2024)
In the contemporary business landscape, the complexity and seriousness of the global issues faced by our society have reached a turning point. Strong multilateral initiatives are needed in order to address the Grand Challenges of our times. Sustainable Open Innovation, characterised by collaborative practices between different partners, driven by sustainability, and transcending the firm’s innovation boundaries, can represent an extremely valuable asset to solve these challenges. This thesis investigates the dynamics of Sustainable Open Innovation between large companies and startups, aiming to elucidate the collaborative process, highlighting the main reasons behind the adoption of Open Innovation mechanisms, as well as presenting the main benefits, challenges and opportunities inherent in such a remarkable innovation approach. Grounded in a multidisciplinary theoretical framework encompassing innovation management, open innovation, sustainability, and finally the interrelation between open innovation and sustainability, this qualitative study employs a mixed-methods approach, through both an inductive and deductive reasoning, and combining semi-structured interviews and secondary data to shed light on the subject matter. The objective of this research is to provide theoretical and practical implication to the recent topic of Sustainable Open Innovation, with a specific focus on effective OI collaborations between large companies and startups. The findings contribute to both theory and practice by advancing our understanding of how large companies and startups can collaborate to foster innovation that is not only profitable and economically viable for both partners, but also socially and environmentally responsible. The results are summarised by taking into account the key research questions addressed in this study, aiming at providing insights on the discussed topic. In the end, this study provides practical recommendations for managers and entrepreneurs seeking to leverage Open Innovation for sustainable development goals.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business